A Method for Exact Error Probability Determination of Nonuniform Signaling For Gaussian Channels - Peric, Z. H.; Bogosavljevic, S. M. (Elektronika ir Elektrotechnika, 2003)
A simple method for exact error probability determination of nonuniform signaling in two dimensions for Gaussian channel is presented in this paper. The error probability is determined using maximal aposteriori probability (MAP) detection principle. Ill. 6, bibl. 7 (in English; summaries in Lithuanian, English, Russian).